Mechanistic study and applications of lanthanide-based upconversion nanomaterials - Wei, Wei (2015)
Owing to the unique spectroscopic properties of lanthanide (Ln) elements, the successful employment of lanthanide-based upconversion (UC) nanomaterials as luminescent biolabels heralds a new era of bioimaging technology. Moreover, their applications in many other fields, such as phototherapy, sensing, solar cells and anti-counterfeiting techniques, are also attracting increasing attention. This makes the investigation on lanthanide-based UC nanomaterials one of the most popular research frontiers in recent years. Although fruitful achievements have been made in this field, further understanding of lanthanide UC mechanism, better synthetic approach to obtain UCNPs with good water dispersibility, and further improvement of their UC efficiency are still issues to be addressed. More specifically, some of the major challenges include: (1) precise manipulation of the UC color output, (2) realization of a rapid strategy to synthesize water-dispersible lanthanide upconversion nanoparticles (UCNPs) for bioimaging application, and (3) their extension to wider applications. The various components of this thesis have attempted to address these challenges. The major contributions presented in this thesis are briefly summarized as follows: (1) The demonstration of cross relaxation (CR) effect as a tool for manipulating the UC color output, and an unprecedented achievement of intense 696 nm emission relying on the CR effect amongst Tm3+ ions; (2) The realization of a facile method for one-step synthesis of size- and phase-controlled water-dispersible NaYF4:Yb/Er UCNPs; (3) The development of a new type of UCNPs-based nanocomposite which may serve as potential laser protective materials.